Predictors of performance during residency in obstetrics and gynecology - Soriano-Estrella, Agnes L. (2010)
The selection of residents for medical specialty programs is one of the most difficult yet crucial tasks facing all selection committees. Typically, data regarding the applicant's demographic profile, previous academic performance and personality characteristics are gathered to determine who among them will have the highest chance of finishing the program and performing well during training. The relationship of each of these data with performance during residency has been extensively studied over the past thirty years. However, results have been inconsistent. Medical residency is a pivotal period in becoming a physician that is universally associated with high levels of intellectual, physical and emotional demands. Several investigators have examined factors that affect the general well-being and performance of residents during training. The Department of Obstetrics and Gynecology of the Philippine General Hospital has utilized a rigid process in the selection of its residents. However, performance of their residence has not been very satisfactory. The present study was therefore undertaken to identify factors present during the application period as well as during training that affect performance during residency at the Department of Obstetrics and Gynecology of the Philippine General Hospital. Files of all residents accepted into the department from 2003 to 2006 and who were able to complete training were reviewed. Demographic data as well as information regarding the following pre-entry variables were collected: medical school attended, average grade at the end of medical school, honors received during medical school, average grade in obstetrics and gynecology subjects during medical school and medical board examination grade. Focus group discussions (FGD) were done to determine factors during residency that affected performance. (FGD) were done to determine factors during residency that affected performance. Outcome measures included the departmental evaluation and in-service rating per year of training. Tests of associations were used to determine significant correlations between independent and dependent variables. Logistic regression was performed on the various pre-residency variables to determine which among them were predictive of residency performance. Content analysis of FGDs was done to identify the more important factors that affect performance of residents during training. Analysis of data showed that the board examination rating was the only pre-entry variable that consistently predicted performance during residency. Performance correlated with the respondent's perception of the level of difficulty per year of training. Likewise, performance was greatly affected by factors present during training that put stress on the residents. These factors included the overwhelming amount of work, adjustments difficulties, lack of control over the tasks assigned to them, strained interpersonal relationships, lack of a sense of gratification, and institutional problems. On the other hand, a good support system, inspiration derived from consultants, job satisfaction, and in inner drive to pursue training in the institution enabled the residents to continue with their training.